Uzņēmuma SIA HC Betons finanšu analīze un novērtējums - Kleina, Baiba (Latvijas Universitāte, 2013)
Diplomdarba nosaukums: Uzņēmuma SIA HC Betons finanšu analīze un novērtējums Diplomdarba mērķis ir uz finanšu analīzes pamata izvērtēt uzņēmuma SIA HC Betons esošo finansiālo situāciju un izstrādāt priekšlikumus finansiālā stāvokļa uzlabošanai. Teorētiskajā daļā apskatīti finanšu analīzes teorētiskie aspekti. Praktiskajā daļā autore veica uzņēmuma SIA HC Betons finanšu analīzi par 2009., 2010., un 2011.gadu. Analītiskajā daļā autore salīdzina rādītājus ar konkurējošo uzņēmumu SIA Cemex. Autore secinājusi, ka uzņēmumam ir finansiālas grūtības, bet pēc autores domām, uzņēmums tuvāko gadu laikā nebankrotēs. Diplomdarba apjoms ir 78 lapaspuses, tas sastāv no 3 daļām, 12 tabulām, 5 attēliem un 12 pielikumiem. Atslēgvārdi: analīze, likviditāte, bankrots, koeficienti.

Diploma thesis: Financial Analysis and Evaluation of Company HC Betons Ltd. The aim of the diploma paper is to evaluate company’s HC Betons Ltd current financial situation based on financial analysis and make suggestions for improvement of the financial position. Theoretical aspects of financial analysis are discussed in the theoretical part of the paper. In the practical part author has performed company’s HC Betons Ltd financial analysis of the years 2009, 2010 and 2011. In the analytical part author compares ratios of a competing company Cemex Ltd. The author concludes that the company is in financial difficulties, but according to the author’s thoughts, the company will not bankrupt in the coming years. The volume of the diploma paper is 78 pages; it consists of 3 parts, 12 tables, 5 images and 12 appendices. Keywords: analysis, liquidity, bankruptcy, ratios.
Financial analysis and evaluation of company HC Betons Ltd
Keywords: Ekonomika